Training reduces catabolic and inflammatory response to a single practice in female volleyball players - Eliakim, A.; Portal, S.; Zadik, Z.; Meckel, Y.; Nemet, D. (The Journal of Strength and Conditioning Research, 2013)
We examined the effect of training on hormonal and inflammatory response to a single volleyball practice in elite adolescent players. Thirteen female, national team level, Israeli volleyball players (age 16.0 ± 1.4 years, Tanner stage 4-5) participated in the study. Blood samples were collected before and immediately after a typical 60 minutes of volleyball practice, before and after 7 weeks of training during the initial phase of the season. Training involved tactic and technical drills (20% of time), power and speed drills (25% of time), interval sessions (25% of time), endurance-type training (15% of time), and resistance training (15% of time). To achieve greater training responses, the study was performed during the early phase (first 7 weeks) of the volleyball season. Hormonal measurements included the anabolic hormones growth hormone (GH), insulin-like growth factor-I (IGF-I) and IGF-binding protein-3, the catabolic hormone cortisol, the proinflammatory marker interleukin-6 (IL-6), and the anti-inflammatory marker IL-1 receptor antagonist. Training led to a significant improvement of vertical jump, anaerobic properties (peak and mean power by the Wingate Anaerobic Test), and predicted VO2max (by the 20-m shuttle run). Volleyball practice, both before and after the training intervention, was associated with a significant increase of serum lactate, GH, and IL-6. Training resulted in a significantly reduced cortisol response ([INCREMENT]cortisol: 4.2 ± 13.7 vs. -4.4 ± 12.3 ng/ml, before and after training, respectively; p < 0.02), and IL-6 response ([INCREMENT]IL-6: 1.3 ± 1.0 vs. 0.3 ± 0.4 pg/ml, before and after training, respectively; p < 0.01) to the same relative intensity volleyball practice. The results suggest that along with the improvement of power and anaerobic and aerobic characteristics, training reduces the catabolic and inflammatory response to exercise.